2022
DOI: 10.1007/s41742-022-00474-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Outbreak on Camping Tourism in Spain: A Spatial Approach to Tourist Destinations

Abstract: The COVID-19 health crisis has wreaked devastation on the world economy, especially on the tourism sector. The camping sector has been little studied despite its high economic impact and participation rate. Moreover, the observable effects of phenomena such as the COVID-19 pandemic have received little research attention. Consequently, the objective of this paper is therefore to analyse the effects of the pandemic on camping tourism by characterising the factors that determine it. The study is carried out by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…3 ), like Lake Garda – which falls into the “Natural Resources” category – while using a picture characterized by the absence of “People”. The latter is particularly important as it arguably resonates with the growing preference for tourists to seek places far from crowds, in the open nature – especially since the COVID-19 outbreak (e.g., Sánchez-Sánchez & Sánchez-Sánchez, 2022 ). Finally, Study 2 showed how the crisis led to a collaboration among competing destinations within the same region, a phenomenon that is described by the strategic management literature as “coopetition”.…”
Section: Discussionmentioning
confidence: 99%
“…3 ), like Lake Garda – which falls into the “Natural Resources” category – while using a picture characterized by the absence of “People”. The latter is particularly important as it arguably resonates with the growing preference for tourists to seek places far from crowds, in the open nature – especially since the COVID-19 outbreak (e.g., Sánchez-Sánchez & Sánchez-Sánchez, 2022 ). Finally, Study 2 showed how the crisis led to a collaboration among competing destinations within the same region, a phenomenon that is described by the strategic management literature as “coopetition”.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Francisca Jesús Sánchez-Sánchez explored camping in Spain using multiple variable analysis techniques. The study concluded that the geographical location of a tourist destination is a decisive factor in the siting of new campsites [16].…”
Section: Campsite Planning Studymentioning
confidence: 99%
“…Camping in general combines inexpensive outdoor accommodation with a form of recreational outdoor activity where individuals spend time -a day or up to several nights -away from home (Brooker and Joppe, 2013;Craig, 2019Craig, , 2020Hewer et al, 2015;Lu et al, 2022;Ma et al, 2020;Radović et al, 2021;Sánchez-Sánchez and Sánchez-Sánchez, 2022). Ma et al (2020) divided camping into three types: tent, recreational vehicle (RV), and cabin.…”
Section: Introductionmentioning
confidence: 99%